El nihilismo de nuestro tiempo. Una crónica. Madrid: Ediciones Encuentro. - Numpaque García, Julián Ramiro (Cuestiones de Filosofia, 2023)
In his work "The Nihilism of Our Time: A Chronicle," Costantino Esposito analyzes nihilism in the contemporary world, using philosophical, literary, aesthetic, and cinematographic references. The author argues that contemporary nihilism is not a loss of values, but rather the search for something irreducible that can be an opportunity to find the meaning of human experience. The article also addresses the crisis of recognition of fundamental duties and values in society, the relationship between nihilism and technology, and the conception of freedom in today's society. In summary, the author highlights that life acquires meaning when confronted with nothingness and that understanding of being arises in moments of lack of meaning.